Effect of organophosphorus pesticides in juveniles of Litopenaeus vannamei alteration of glycogen, triglycerides, and proteins - Osuna-Flores, Israel (Ecotoxicology (London, England), 2019)
The presence of pesticides has recently been reported in shrimp farms adjacent to agricultural areas on the east coast of the Gulf of California. This study assessed the possible effect of organophosphorus pesticides in the coastal environment of Sinaloa, México, using the white shrimp Litopenaeus vannamei as a bioindicator since their presence, abundance or behavior indicate some process or state of the system in which they live. Sublethal bioassays were performed on shrimps in intermolt state using commercial brands of organophosphorus pesticides, chlorpyrifos (0.0015 mg l-1), diazinon (0.0120 mg l-1), methamidophos (1.207 mg l-1), azinphos-methyl (0.0101 mg l-1), and methyl parathion (0.0075 mg l-1) were tested. Results showed reductions in glycogen, triglycerides, and total protein concentrations in shrimp muscle, except for the diazinon treatments, in which an increase in triglyceride level was detected. The observed alterations in the three cellular components were probably due to the metabolic compensation mechanism of the shrimp in reaction to the stress produced by organophosphorus pesticides, which act as endocrine disruptors. The establishment of continuous environmental monitoring programs of the coastal zone of Northwestern Mexico is strongly recommended